Expression of gap junctions bearing connexin-43 subunits and glial fibrillary acidic protein in the rat dorsal root ganglia following hind paw incision - Deshmukh, Vishwajit Ravindra; Prasoon, Pranav; Ray, Subrata Basu (International Journal of Research in Medical Sciences, 2016)
Background: Dorsal root ganglion (DRG) neurons mediate the transmission of sensation from the periphery. DRG neurons are pseudounipolar in nature and enveloped by the satellite glial cells (SC). Satellite glial cells have been reported to influence neuronal excitability via gap junctions. Postoperative pain causes induction of various neurotransmitters such as connexin-43 and glial fibrillary acidic protein (GFAP), in the satellite cells surrounding neuronal cell bodies Objective: To study the expression of connexin-43 and Glial fibrillary acidic protein after hind paw incision. Methods: Male adult Sprague-Dawley rats (n=12) were used. Rats were randomly divided into two groups. Group I (n=6) and Group II (n=6) for immunohistochemical study with glial fibrillary acidic protein (GFAP) and connexin-43 (Cx-43) respectively. In this study, rats were subjected to noxious stimuli on the right hind paw under general anesthesia. Dorsal root ganglia of both sides (L4 spinal nerves) were isolated after transcardiac fixation with 4% paraformaldehyde. The ganglia from the non-incised side were taken as the control group. Results: Unipolar neurons in the DRG were surrounded by satellite cells. The satellite cells were positive for GFAP, which showed increased expression on the surgical side after noxious stimuli. Cx-43 immunostaining also showed an increased expression in the periphery of neuronal cell bodies of surgical side representing the location of gap junctions and hyperexcitability of neurons. Conclusions: Small to medium sized neurons carry pain sensation from the periphery to the central nervous system. Increased gap junctions were noted in small neurons and satellite cells after surgery. Gap junctions might contribute to increased excitability of small neurons in postoperative pain.